2022
DOI: 10.4102/sajhivmed.v23i1.1362
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of health-related quality of life in young adults living with perinatally acquired HIV infection in Botswana

Abstract: Background: Due to the successful antiretroviral therapy (ART) programme in Botswana, large numbers of perinatally HIV-infected adolescents are emerging into young adulthood. Young adulthood is a critical period of human development. However, there is lack of information on the factors affecting the health-related quality of life (HRQOL) of young adults living with perinatally acquired HIV (YALPH) in Botswana.Objectives: The objective of this study was to assess the HRQOL and its determinants among YALPH who w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…However, this frequency aligns with what has been reported in other studies focusing on HIV-positive women, indicating a consistent pattern of sexual dysfunction among HIV-positive women across different geographical and cultural contexts [ 25 , 48 50 , 69 ]. Previous studies reported an association between HIV infection and poor quality of life resulting from physical, psychological, or emotional factors [ 6 8 , 13 , 18 ]. Medical conditions, including HIV infection, reduce the quality of life and thus impact sexual function [ 11 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this frequency aligns with what has been reported in other studies focusing on HIV-positive women, indicating a consistent pattern of sexual dysfunction among HIV-positive women across different geographical and cultural contexts [ 25 , 48 50 , 69 ]. Previous studies reported an association between HIV infection and poor quality of life resulting from physical, psychological, or emotional factors [ 6 8 , 13 , 18 ]. Medical conditions, including HIV infection, reduce the quality of life and thus impact sexual function [ 11 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies in sub-Saharan Africa and other parts of the world have examined the health-related quality of life in HIV-infected persons, with most studies emphasizing the physical, mental, and social aspects of quality of life while leaving out the sexual function component [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. The few studies that addressed some aspect of sexual functioning were either limited by sample size or did not use a globally accepted and validated tool, such as the Female Sexual Function Index questionnaire, in conducting their study [11,15,17].…”
Section: Introductionmentioning
confidence: 99%
“…Others, mainly single centre cohorts, report lower rates of educational attainment and employment in both groups (PaHIV and HEU) when compared to age-matched population norms [ 31 , 38 , 45 ]. In Botswana (PaHIV, ages 18–30), the overall health-related QOL was good, with outcomes significantly associated with education, employment, viral suppression and self-reported illness [ 46 ]. However, those with disability, neurocognitive impairment, care leavers, young parents and the unemployed were the most vulnerable, reporting a poorer QOL [ 47 ].…”
Section: Neurocognitive Mental Health and Quality Of Life Outcomes In...mentioning
confidence: 99%
“…25,[45][46][47]50 Previous studies reported an association between HIV infection and poor quality of life resulting from physical, psychological, or emotional factors. [6][7][8][9][10] Medical conditions, including HIV infection, reduce the quality of life and thus impact sexual function. 20,21 Findings in this study support this assertion, as a co-morbid medical condition (aOR: 1.8; 1.1 -3.0) and patients' health questionnaire scores of at least 10 (aOR: 2.3; 1.7 -3.2) retained independent statistically significant association with sexual dysfunction after controlling for potential confounding variables.…”
Section: Risk Factors For Sexual Dysfunction Among the Cohortmentioning
confidence: 99%
“…6,7 Numerous studies in sub-Saharan Africa have examined the health-related quality of life in HIV-infected persons, with most studies emphasizing the physical, mental, and social aspects of quality of life while leaving out the sexual function component. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] The few studies that addressed some aspect of sexual functioning were either limited by sample size or did not use a globally accepted and validated tool, such as Female Sexual Function Index questionnaire, in conducting their study. [19][20][21] Few studies focused on sexual dysfunction among HIV-positive women, even though a high prevalence of sexual dysfunction in persons living with HIV/AIDS has been reported .…”
Section: Introductionmentioning
confidence: 99%